Cannabidiol Inhibits Inflammation Induced by Cutibacterium acnes-Derived Extracellular Vesicles via Activation of CB2 Receptor in Keratinocytes - Jiang Z; Jin S; Fan X; Cao K; Liu Y; Wang X; Ma Y; Xiang L (Dove Medical Press, 2022)
Ziqi Jiang,* Shanglin Jin,* Xiaoyao Fan, Ke Cao, Ye Liu, Xuan Wang, Ying Ma, Leihong Xiang Department of Dermatology, Huashan Hospital, Fudan University, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Leihong Xiang; Ying Ma, Department of Dermatology, Huashan Hospital, Fudan University, No. 12 Wulumuqizhong Road, Shanghai, 200040, People's Republic of China, Tel: +86 21 52889999, Fax: +86 21 62489191, Email flora_xiang@vip.163.com; alle_ma@163.comBackground: Acne is a common inflammatory skin disease, while cannabidiol (CBD) is a representative non-psychoactive phytocannabinoid which has been proved to exert universal anti-inflammatory properties. This study aimed to explore the effect of CBD on acne inflammation induced by Cutibacterium acnes-derived extracellular vesicles (CEVs) in keratinocytes and reveal the underlying mechanisms.Methods: Normal human epidermal keratinocytes (NHEKs) were stimulated by CEVs in the presence of CBD or vehicle. Interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α levels were examined by RT-PCR and ELISA. The expression of cannabinoid type-2 (CB2) receptor and transient receptor potential vanilloid type-1 (TRPV1) was detected by Western blotting. TNF-α levels in the presence of CB2 receptor antagonist (AM630) or TRPV1 antagonist (Capsazepine) were detected by RT-PCR. The activation of MAPK and NF-κB signaling pathways and the nuclear translocation of NF-κB p65 upon CBD treatment were analyzed by Western blotting and immunofluorescence assay, respectively.Results: The expression of inflammatory cytokines (IL-6, IL-8 and TNF-α) in CEVs-stimulated NHEKs was suppressed by CBD. CB2 receptor expression was upregulated by CBD, whereas CEVs-promoted TRPV1 expression was downregulated by CBD. AM630 reversed TNF-α levels inhibited by CBD. Capsazepine exerted an inhibitory effect on CEVs-induced inflammation and had synergistic effect with CBD. The phosphorylation of ERK1/2 and NF-κB p65 and nuclear translocation of NF-κB p65 were induced by CEVs but reduced by CBD.Conclusion: The results indicated that CBD could inhibit inflammation induced by CEVs in NHEKs, which was mediated by activation of CB2 receptor and enhanced by the TRPV1 antagonist, through inactivation of the MAPK and NF-κB signaling pathways. CBD might be a potential novel strategy for acne treatment in the future.Keywords: cannabidiol, acne, inflammation, Cutibacterium acnes, keratinocytes